Approaching Gender and Sexuality Issues from a Sociolinguist Corpus-Based Analysis: A Methodologic Challenge - Rodrigues, Angélica [UNESP]; Clempi, Camila Bordonal [UNESP]; De Almeida Arruda Felix, Rafael [UNESP] (Springer Nature, 2023)
Different researches in the field of sociolinguistics consider the gender/sex variant as a relevant aspect of social stratification. In this chapter, we aim to discuss how to approach the issue of social gender and sexuality, combining sociolinguistic research and social theory of gender and sexuality. The main question that we must address concerns mainly the elaboration of linguistics corpora and the analysis of speech and writing data concerning the implementation of periphrastic future in Brazilian Portuguese and the use of superlative for gay man in Brazilian gay community, willing to validate our socially verifiable hypotheses about the influence of gender and sexuality in the processes of linguistic variation and change.
Keywords: Gender; Linguistic variation and change; Periphrastic future; Sexuality; Superlatives